PENGOLAHAN LIMBAH RUMAH TANGGA TERPADU MENJADI SUMBER ENERGI ALTERNATIF DI DESA GLAGAHARUM - Mochamad Syahrul Gunawan; Niken Ayu Aprilia; Wanda Dwi Pebrianti; M. Hasan Abdullah (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
ABSTRACT The increasing population causes the amount of waste to increase. Glagaharum Village has 20 RT and 4 RW located in Porong District, Sidoarjo Regency. A total of 5 RTs were affected by the Lapindo mudflow, resulting in land narrowing. Garbage from residents is dumped on vacant land and burned. The combustion process is not perfect so that it triggers environmental pollution of both soil, water and air. Based on these problems, a solution is needed to overcome the amount of waste. Among them by processing household waste into alternative energy sources with pyrolysis and biogas technology. These solutions can be implemented through community empowerment programs. The community empowerment method is carried out offline according to health protocols. The stages in the program include, 1) FGD (Forum Group Discussion), 2) Program introduction socialization, 3) Pretest & posttest, 4) Design of technological inventions, 5) Training and 6) Evaluation. The results of community empowerment are, 1) There is a change in community knowledge which is marked by a change in the value of the pretest and posttest, 2) There is a physical change in the community which is indicated by the existence of an integrated waste processing unit and the community as the manager and person in charge of the unit.